The relationship between load-velocity profiles and 50 m breaststroke performance in national-level male swimmers - Olstad, B. H.; Hunger, L.; Ljødal, I.; Ringhof, S.; Gonjo, T. (Journal of Sports Sciences, 2024)
This study investigated the relationships between load-velocity profiling and 50 m breaststroke performance. Twenty-seven male swimmers qualified for the national championship participated and performed a 50 m breaststroke trial with a multicamera system. The total race time (t50 m), forward velocity during surface swimming (v50 m), stroke length, and stroke frequency were obtained from the automatic post-processing of the system. Afterwards, the participants performed semi-tethered swimming with three external loads using a robotic resistance device. The average velocity from three stroke cycles was plotted as a function of the corresponding load. The theoretical maximum velocity (v0) and load (L0), L0 normalized to body mass, steepness of the regression line (slope), and active drag (AD) were calculated. The main findings were moderate to large correlations of two 50 m race variables (t50 m and v50 m) with v0, L0, and AD (t50 m range: r = -.444 to r = -.619, p = .020 to p = .001), (v50 m range: r = .451 to r = .568, p = .018 to p = .002). This shows the importance of applying maximum propulsive force to achieve high swimming performance and that load-velocity profiling is an indicator of 50 m breaststroke performance. Load-velocity measurements over time can also monitor velocity, strength, and drag-minimizing abilities, explaining performance changes and training effects.